2013
DOI: 10.2134/agronj2012.0337
|View full text |Cite
|
Sign up to set email alerts
|

Validating the FAO AquaCrop Model for Rainfed Maize in Pennsylvania

Abstract: It is widely known that a close relationship exists between crop production and water stress. In this study, field‐measured data were used to test the performance of AquaCrop and its ability to capture this relationship for rainfed maize (Zea mays L.) in Pennsylvania. The objectives were to evaluate AquaCrop’s ability to simulate the progression of cumulative biomass and grain yield with time, final biomass and harvestable yield, and volumetric water content at six depths. Two years of data from a study conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 11 publications
9
28
0
Order By: Relevance
“…Measurements showed that SWC was more variable in the upper soil layers implying that roots were mostly active in extracting water from the upper soil layers. This is in agreement with the finding of Cabelguenne and Debaeke (1998), who reported that maize extracts most water from the top 0.5 m; therefore accurate simulation of SWC in this zone would positively influence simulated maize development and yield (Mebane et al 2013;Araya et al 2010b). In top soil layers, maize root density and its spatial variability is very high (Trachsel et al 2013); therefore detailed information of root length density, specific root length, and precisely-determined root distribution in AquaCrop considerably leads to more accurate simulations of SWC as it directly affects the simulation of transpiration.…”
Section: Soil Water Contentsupporting
confidence: 92%
See 2 more Smart Citations
“…Measurements showed that SWC was more variable in the upper soil layers implying that roots were mostly active in extracting water from the upper soil layers. This is in agreement with the finding of Cabelguenne and Debaeke (1998), who reported that maize extracts most water from the top 0.5 m; therefore accurate simulation of SWC in this zone would positively influence simulated maize development and yield (Mebane et al 2013;Araya et al 2010b). In top soil layers, maize root density and its spatial variability is very high (Trachsel et al 2013); therefore detailed information of root length density, specific root length, and precisely-determined root distribution in AquaCrop considerably leads to more accurate simulations of SWC as it directly affects the simulation of transpiration.…”
Section: Soil Water Contentsupporting
confidence: 92%
“…It is most likely that the measured SWC in 67 DAP in calibration are not correct since the SWC in the top soil layer is below or equal to PWP. Mebane et al (2013) used AquaCrop to simulate SWC of two rainfed maize experiments in Pennsylvania and reported RMSEs of 0.025 and 0.044 m 3 m −3 , which agree with the results of our study. Other studies have also reported satisfactory performance of AquaCrop in simulating SWC of various crops, for instance quinoa (Geerts et al 2009), barley (Abrha et al 2012), Soil water depletion threshold above which canopy expansion starts declining, P upper 0.2 Soil water depletion threshold above which canopy expansion ceases, P lower 0.5…”
Section: Calibration and Validation Of Aquacropsupporting
confidence: 89%
See 1 more Smart Citation
“…The model is developed to simulate the yield response of crops as a function of water consumption . The elements of the AquaCrop soil-plantatmosphere continuum focus on (i) the soil water balance, (ii) the plant's development, growth, and yield processes, and (iii) the atmospheric temperature regime, evaporative demand, rainfall and CO 2 concentration Mebane et al, 2013). Compared to other crop growth models, AquaCrop uses a significantly smaller number of input parameters to predict daily biomass and water requirement ).…”
Section: Soil Water Balance and Crop Growth Modellingmentioning
confidence: 99%
“…The global applicability of AquaCrop is dependent on its being tested in a diverse environment under differing soil conditions, crops, agronomic practices, and climatic conditions [32,33] . For example, the calibration and evaluation of the performance of AquaCrop has been carried out for quinoa [34] , wheat [35][36][37][38][39] , sorghum [40] , maize [28,[41][42][43][44][45][46] , potato [32,47] , and cabbage [48,49] . Previous studies have demonstrated that AquaCrop is able to accurately simulate crop canopy cover, biomass yield and grain yield in diverse environments and under a variety of meteorological conditions and management practices.…”
Section: Introductionmentioning
confidence: 99%